Investigating the impacts of using enterprise resource management solutions by micro and small businesses (Research, Society and Development, 2024)
Small businesses face several challenges in our country, such as lack of financial resources, cash flow and time management, competition, access to credit, etc. Many of them have a very early level of technological maturity, making it even more difficult for these companies to survive in a competitive environment. The area of ​​digital transformation has sought to present new ways for companies to operate with the support of the use of digital technologies. E-commerce solutions, digital marketing, and pricing are some examples of technologies that can boost the business of these companies. However, many of them still need to understand more basic processes that are supported by enterprise resource planning (ERP) systems. These systems are shown to be basic initial solutions for companies to start taking the first steps towards digital transformation. SEBRAE has programs that support micro and small companies in the use of technologies. One example is the Local Innovation Agents (ALI) Digital Transformation program, which supports companies in the use of technologies. The objective of this study is to investigate the impacts of the use of enterprise resource management solutions by micro and small companies in the context of the ALI program. Both the quantitative numbers of the program regarding the use of ERP tools in small businesses were analyzed. The data analysis highlights the impacts of the use of ERP in these companies, pointing out directions to enhance actions in favor of a digital transformation of micro and small entrepreneurs.